A novel kerf‐free wafering process combining stress‐induced spalling and low energy hydrogen implantation. Issue 10 (11th July 2016) - Pingault, Timothée; Pokam‐Kuisseu, Pauline Sylvia; Ntsoenzok, Esidor; Blondeau, Jean‐Philippe; Ulyashin, Alexander; Labrim, Hicham; Belhorma, Bouchra
Abstract: In this work, we studied the potential use of low‐energy hydrogen implantation as a guide for the stress‐induced cleavage. Low‐energy, high fluence hydrogen implantation in silicon leads, in the right stiffening conditions, to the detachment of a thin layer, around a few hundreds nm thick, of monocrystalline silicon. We implanted monocrystalline silicon wafers with low‐energy hydrogen, and then glued them on a cheap metal layer. Upon cooling down, the stress induced by the stressor layers (hardened glue and metal) leads to the detachment of a thin silicon layer, which thickness is determined by the implantation energy. We were then able to clearly demonstrate that, as expected, hydrogen oversaturation layer is very efficient to guide the stress. Using such process, thin silicon layers of around 710 nm‐thick were successfully detached from low‐energy implanted silicon wafers. Such layers can be used for the growth of very good quality monocrystalline silicon of around 50 µm‐thick or less. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)